Self-dehumanisation in voice hearers: the end of a continuum - O’Brien-Venus, Bethany; Jenkins, Tom; Chadwick, Paul (Frontiers in Psychiatry, 2023)
Abstract Background Meta-dehumanisation and self-dehumanisation have been identified as potentially relevant phenomena for developing a deeper understanding of distress related to voice-hearing, particularly those experiencing voices as part of psychosis. Chadwick (2019) has previously argued that those with psychosis, including those who hear distressing voices, typically feel “dehumanised and set apart by their experiences of psychosis and trauma”. The present study explores the subjective experience of self-dehumanisation in people who experience distressing voices, which was selected as a useful starting point to inform future research focused on understanding dehumanisation in people with psychosis. Method Qualitative data was obtained through twenty semi-structured interviews with self-identifying voice hearers and analysed using reflexive thematic analysis. This followed the recursive six phase procedure of Braun and Clarke (2022), and this was conducted from a critical realist, contextualist position. Results Reflexive thematic analysis of participant’s experiences produced a core theme, Dehumanisation as the End of Experiential Continua, and six subthemes: Extent of Distressing Sensory Fragmentation; Sense of Belonging with Other Humans; Integrity of Self as a Private, Coherent Entity; Sense of Worth as a Human Being; Strength of Personal Agency; and Trust in Own Credibility and Reliability. Two further themes, The Push and Pull of Dehumanising Forces and Reclaiming Life through Humanising Forces, were identified. Findings were presented to a panel of five experts by experience, all with lived experience of psychosis and service-use; all five strongly endorsed the themes as fitting with and expressing their own experiences of self-dehumanisation. Conclusions Reflexive thematic analysis of voice hearers’ accounts identified self-dehumanisation as the endpoint where six experiential continua coalesce. Experiential movement along these continua was affected by a range of interpersonal, intrapersonal, and societal forces over time, including dehumanising attitudes of others and voice malevolence and omnipotence. Future research might examine if and how psychological therapies aimed at those experiencing distressing voices, such as people experiencing psychosis may address feelings of self-dehumanisation. Key Words Voice-hearing; Thematic Analysis; Self-dehumanisation; Meta-dehumanisation; Psychotic Phenomena